2008
DOI: 10.1890/07-1682.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Contagiousness of Canopy Disturbance in Tropical Rain Forest: An Individual‐tree‐based Test

Abstract: Spatial contagiousness of canopy dynamics-the tendency of canopy disturbances to occur nearby existing canopy openings due to an elevated risk of tree fall around gaps-has been demonstrated in many temperate-zone forests, but only inferentially for tropical forests. Hypothesized mechanisms increasing the risk of tree fall around tropical forest gaps are (1) increased tree exposure to wind around gaps, (2) reduced stability of trees alongside gaps due to crown asymmetry, or (3) reduced tree health around gaps d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 56 publications
3
23
0
Order By: Relevance
“…As shown by our model, the inherent variations of forest AGB stock and mortality are quite different, and more sampling efforts are required to obtain a reliable AGB dynamic than standing stock. Similar results were found by Jansen et al (2008), who indicated that at least 9-ha area would be needed to estimate AGB increment but at least 40 ha to reliable estimate AGB loss. Compared with mortality of seedling and small trees, disturbance-driven deaths of dominant, big trees that have greater impact on stand biomass accumulation are rare and intermittent (Berger et al, 2004).…”
Section: Mortality Shapes the Agb Changesupporting
confidence: 85%
“…As shown by our model, the inherent variations of forest AGB stock and mortality are quite different, and more sampling efforts are required to obtain a reliable AGB dynamic than standing stock. Similar results were found by Jansen et al (2008), who indicated that at least 9-ha area would be needed to estimate AGB increment but at least 40 ha to reliable estimate AGB loss. Compared with mortality of seedling and small trees, disturbance-driven deaths of dominant, big trees that have greater impact on stand biomass accumulation are rare and intermittent (Berger et al, 2004).…”
Section: Mortality Shapes the Agb Changesupporting
confidence: 85%
“…square meters of canopy loss). As such, it remains unknown whether any given gap is shrinking due to regeneration or growing due to adjacency effects from neighboring individuals [59], [60]. The best way around this problem is to image canopy disturbances directly to derive recent disturbance events.…”
Section: Discussionmentioning
confidence: 99%
“…Our own analyses found no spatial autocorrelation in biomass change within the plot (Figure 14.2), suggesting that this assumption is appropriate for our site. The direct causal influence between patches is, in general, likely to be small most of the time; although gaps are commonly believed to be contagious and may be modelled as such (Sole & Manrubia 1995), a recent study found that areas next to existing canopy gaps have disturbance rates that are similar to those of areas far from existing gaps (Jansen, Van der Meer & Bongers 2008). On the other hand, large-scale disturbances, e.g.…”
Section: E T E C T I N G a N D P R O J E C T I N G C H A N G E S I mentioning
confidence: 99%